Mapping the evolution of employee creativity and innovation in the sphere of business and management: a bibliometric analysis in the early 21st century - Tapaswini Panda; T. N. V. R. L. Swamy (Cogent Business & Management)
This study presents a comprehensive bibliometric and content analysis of employee creativity and innovation research in business and management from 2001 to 2024. Using data from Scopus and Web of Science, the study applies co-occurrence analysis, thematic mapping, and social network analysis to uncover intellectual and conceptual structures in the field. This analysis identifies five thematic domains: (1) Leadership and Employee Creativity, (2) Organizational and Institutional Contributions, (3) Regional and Cultural Contexts of Innovation, (4) Thematic Evolution from Individual to Structural Perspectives, and (5) Underexplored Psychological Constructs in Creativity. The findings highlight the increasing focus on leadership’s role in fostering innovation, the transformative influence of AI, and the importance of cultural intelligence in shaping creative behaviors. Co-citation network analysis reveals strong linkages between leadership styles and innovation outcomes, while thematic evolution suggests a transition from broad creativity research to more nuanced studies on digital transformation and knowledge-sharing. Despite growing research interest, gaps remain in understanding market-driven innovation, self-efficacy, and cultural diversity in creativity. By mapping the intellectual trajectory of the field, this study provides insights for scholars and practitioners, emphasizing emerging themes such as AI-enabled creativity, sustainability-driven innovation, and the need for cross-cultural perspectives in organizational creativity research.